2017
DOI: 10.2147/ijn.s146505
|View full text |Cite
|
Sign up to set email alerts
|

&alpha;<sub>v</sub>&beta;<sub>3</sub> integrin-targeted micellar mertansine prodrug effectively inhibits triple-negative breast cancer in vivo

Abstract: Antibody-mertansine (DM1) conjugates (AMCs) are among the very few active targeting therapeutics that are approved or clinically investigated for treating various cancers including metastatic breast cancer. However, none of the AMCs are effective for the treatment of triple-negative breast cancers (TNBCs). Here, we show that cRGD-decorated, redox-activatable micellar mertansine prodrug (cRGD-MMP) can effectively target and deliver DM1 to α v β 3 integrin overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Zhong and co-workers formulated cRGD-decorated, redox-activatable micellar mertansine prodrug to deliver mertansine to αvβ3 integrin overexpressed triple negative breast cancer. The cytotoxicity analysis showed that these micelles effectively suppressed MDA-MB-231 breast tumor growth without causing obvious side effects, as revealed by the body weight loss and histological analysis [ 224 ]. The formulation was effective in targeting and delivering of mertansine to α v β 3 integrin overexpressing triple negative breast cancer with a potent tumor growth inhibition.…”
Section: Polymeric Micellesmentioning
confidence: 99%
“…Zhong and co-workers formulated cRGD-decorated, redox-activatable micellar mertansine prodrug to deliver mertansine to αvβ3 integrin overexpressed triple negative breast cancer. The cytotoxicity analysis showed that these micelles effectively suppressed MDA-MB-231 breast tumor growth without causing obvious side effects, as revealed by the body weight loss and histological analysis [ 224 ]. The formulation was effective in targeting and delivering of mertansine to α v β 3 integrin overexpressing triple negative breast cancer with a potent tumor growth inhibition.…”
Section: Polymeric Micellesmentioning
confidence: 99%
“…Recently, Zhong et al. utilized a PD functionalized polymer to deliver a fluorescent dye, 1,1′‐dioctadecyltetramethyl indotricarbocyanine iodide (DiR), into MDA‐MB‐231 tumor‐bearing mice for in vivo fluorescence imaging . DiR was encapsulated by the polymer to fabricate polymeric micelles, which were further modified with tumor targeting ligand RGD.…”
Section: Applications Of Pd Modified Polymersmentioning
confidence: 99%
“…In vivo fluorescence imaging of MDA‐MB‐231 tumor‐bearing mice after intravenous injection with DiR‐loaded polymeric micelles A) with and B) without RGD decoration. Reproduced with permission . Copyright 2017, DOVE Medical Press.…”
Section: Applications Of Pd Modified Polymersmentioning
confidence: 99%
“…Effective internalization by TNBC cells is a prerequisite for chemotherapy drugs to kill the tumour cells. In this work, the RGD-MBs + UTMD were designed to promote drugs internalization and further improve the treatment effect to TNBC cells by delivering more RGD-MBs around tumour cells through peptide RGD, 17 and punching transient holes on the cells membrane surface by sonoporation effect inducing by UTMD. 11 The internalization and intracellular distribution of the RGD-MBs in TNBC cells (MDA-MB-231) were observed through uorescence inverted microscope.…”
Section: Improved Drug Internalization and Inhibited Proliferation Ofmentioning
confidence: 99%
“…16 In this work, we designed a drug carrier system, PTX-loaded RGD-lipid microbubbles (PTX@RGD-MBs) combining ultrasonic targeted microbubble destruction (UTMD), by the thin-lm hydration-sonication method (Fig. 1), where RGD peptide (three peptides, arginine-glycine-aspartic acid) as tumour active targeting peptide to precisely guide microbubbles to TNBC cells, [17][18][19] PTX in oil layer as chemotherapeutic agent to kill TNBC cells, sulfur hexauoride (SF 6 ) as internal gas of microbubbles to generate contrast enhanced ultrasound (CEUS) images through the nonlinear harmonics, 20 along with UTMD to promote PTX's internalization. 21 As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%